Exercise habits and ageing health : exploring the associations of FGF21 and lung microbiome in glycaemic regulation, bone health, arterial stiffness and respiratory health - Lee, Shuen Yee (Nanyang Technological University, 2020)
Advancing age causes progressive decline in physiological functions and increases the risk of diseases and death. Age is an independent predictor of non-communicable chronic diseases such as bone fragility and respiratory and metabolic diseases, including cardiovascular disease and type 2 diabetes mellitus (T2DM). Besides age, there is good consensus among researchers and professional institutions that physical inactivity is another important factor that increases the risk of age-associated chronic diseases. Contralaterally, there is much research evidence supporting the effects of exercise in preventing and mitigating the effects of age-associated chronic conditions. Age-associated chronic disease accounted for ~71% of deaths globally and with the projected two-fold increase in elderly population worldwide by 2050, age-associated chronic disease-related mortality rate is also projected to increase exponentially in the next three decades. The increasing burden of age-associated chronic disease globally implies the sub-optimal effectiveness of existing healthcare models and therapeutics in treating and controlling these conditions at the population level. While it is not possible to reverse the growth of older population, more can be done through biomedical research to understand better the mechanisms underlying the favourable effects of exercise on ageing health, which may lead to potential therapeutic targets for preventing or decelerating the risk of age-associated chronic diseases. There is growing interest in the therapeutic role of fibroblast growth factor 21 (FGF21) and the microbiome in age-associated conditions. The primary aim of this thesis was to investigate the associations of FGF21 with the effects of age and habitual exercise on glucose regulation, bone mass, oxidative stress and arterial stiffness. The thesis also explored the effects of age on lung microbiome and the associations with arterial stiffness and lung function. The aims of the thesis were investigated through a review of relevant research evidence and four studies.